The relation between early self‐regulation and classroom context: The role of adult presence, the task's source of initiation, and social context. (7th December 2021) - Zachariou, Antonia; Whitebread, David
Abstract : Background: Recent research emphasizes the role of the classroom context in promoting self‐regulation development. However, the results are equivocal. Additionally, research tends to focus on studying the two extremes of classroom contexts (e.g., teacher fully involved vs. teacher absent during a task), which does not represent the everyday reality of the classroom. Aims: To explore the extent to which children's self‐regulation differs across activities with different instructional characteristics, while adopting a fine‐grained approach, which explores the middle ground between the two extremes of classroom contexts. Sample: The participants were 36 children aged 6–8 (50% female). Methods: The children participated in a variety of activities in classroom contexts that differed in terms of: (1) level of teacher involvement, (2) whether activities were teacher‐initiated and ‐led or child‐initiated and ‐led, and (3) social context, that is, individual, pair, or group tasks. More than 15, 000 micro‐episodes of self‐regulatory behaviours were coded, based on the C.Ind.Le coding framework. Results and Conclusions: The classroom context had an effect on children's self‐regulation rates. The children showed significantly more self‐regulation when the teacher was absent, compared to involved in the activity, and more self‐regulation when the teacher was involved compared to just present. More self‐regulation was evident when the activity was either completely teacher‐initiated and led or child‐initiated and led, compared to teacher‐initiated but child‐led. Finally, the rate of self‐regulation was significantly higher in pair and individual activities, compared to larger‐group activities. These findings could support policy and practice to promote contexts that encourage self‐regulatory development.